PENGGUNAAN RESAMPLING DALAM PENGGAMBARAN QUICK COUNT - ADI SETIAWAN (Department of Mathematics, Universitas Negeri Gorontalo, 2020)
In this paper a descriptive statistical analysis of the results of the 2019 presidential election was presented related to the quick count result. Descriptive statistical analysis was also conducted on the results of the 2019 presidential election in Salatiga City (Central Java province), Solok City (West Sumatra province) and Rejang Lebong Regency (Bengkulu province). The resampling method is used to illustrate how the quick count method can be explained for finite populations in Salatiga City, Solok City and Rejang Lebong Regency. By using resampling, the percentage obtained by the Jokowi-Amin pair in Salatiga, Solok and Rejang Lebong are 78.05%, 87.86% and 56.85%, whereas the reality for the three cities in a row is 78.03%; 87,79% and 56.36%.